Cover Image, Volume 66, Issue 1. Issue 1 (1st December 2016) - Li, Hong; Caire da Silva, Lucas; Schulz, Michael D; Rojas, Giovanni; Wagener, Kenneth B
Abstract : The cover image, designed by Dr. Paula Delgado, is based on the Mini‐review A review of how to do an acyclic diene metathesis reaction DOI:10.1002/pi.5188, by Kenneth B. Wagener et al. Abstract : The cover image, designed by Dr. Paula Delgado, is based on the Mini‐review A review of how to do an acyclic diene metathesis reaction DOI:10.1002/pi.5188, by Kenneth B. Wagener et al.